The interaction between human blood-group (AB0) substances and enteropathogenic bacterial agents - Çevik, Necla; Büyükgebiz, Benal (The Turkish Journal of Pediatrics, 1987)
A total of 592 patients with diarrheal disorders, aged between 0 and 15 years, seen at the "Diarrheal Diseases and Oral Rehydration Therapy Research and Training Center" of the Hacettepe University Institute of Child Health between May 1, 1986 and January 1, 1987 were studied to determine the interaction between human blood-group (AB0) substances in infants and young children and enteropathogenic bacterial agents. The controls consisted of 237 healthy infants and children without any diarrheal disorders. 244 (44.6%) patients and 90 (40%) controls had blood group A, 177 (32.5%) patients and 76 (32%) controls blood group 0, 92 (16.8%) patients and 44 (18.7%) controls blood group B and 34 (6.1%) patients and 21 (8.8%) controls blood group AB. Shigella was isolated from 21 (36.8%) patients and both Salmonella and enteropathogenic E.coli from 18 (31.8%) patients. While the related literature indicates a significant increased susceptibility of blood groups B and AB in regard to Gram-negative enteric pathogens (except Shigella), our preliminary study did not reveal any statistical significant difference between the blood groups.